115 Virtual consultations: The experience of Oncology and Palliative care healthcare professionals 'One size doesn't fit all'. (14th March 2023) - Lewis, Heledd; Taubert, Mark; Nelson, Annmarie
Abstract : Introduction: To maintain continuity of care during the Covid-19 pandemic, virtual consultations (VC) became the mainstay of patient practitioner interactions. Prior to this, little was understood regarding healthcare professionals' (HCP) experiences in translating their care to this modality. Aim: Exploration of oncology and palliative care HCP perspectives on VC, the role of VC in varying stages of the treatment and management of patient care, and the future role of VC in patient care. Method: A cross sectional mixed methodology observational study of oncology and palliative care HCPs, analysed via an inductive thematic approach. Results: 87 surveys completed within a one-month period. Three master themes were identified. Personal, professional, and familial factors included factors of patient age, illness and VC skill in influencing HCPs' experience of VC. Relationships and connection highlighted the influence of VC in empowering patients, the importance of a therapeutic relationship. Here, there was a perceived loss in these domains with VC. Significant challenges were felt in sharing bad news and having challenging conversations. Many survey respondents emphasized that they preferred to have first time consultations face-to-face, and not virtually. Within the domain of logistical and practical implications reduced travel and increased accessibility were seen as a benefit of VC. The inability to examine patients and concerns regarding missing clinical signs was emphasised as a significant barrier, alongside the challenges faced with sometimes failing technology. Conclusion: VCs have a stronger role for those patients who are already known to professionals, when prior relationships have already been developed, and here they are perceived as practical and beneficial. VC for difficult discussions and for unstable patients were felt to be inadequate. Triaging patients with regard to suitability prior to offering VCs, with emphasis on the importance of patient choice, were seen as priority areas in this new era of VCs.